1993
DOI: 10.1152/jappl.1993.75.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methacholine on low-frequency mechanics of canine airways and lung tissue

Abstract: We measured tracheal flow, tracheal pressure, and alveolar capsule pressure in four anesthetized paralyzed tracheostomized open-chest dogs. Lung impedance between 0.12 and 4.88 Hz was measured with a forced volume oscillation technique before and after the intravenous administration of methacholine (MCh). Before MCh administration, lung impedance was well described by a model featuring a single airway leading to an alveolar region surrounded by tissue with a continuous distribution of viscoelastic time constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Other investigators have reported that models which include terms for bronchial compliance, peripheral resistance, inhomogeneity or tissue properties may be superior to a SCM. 3,11,12 The visco-elastic tissue properties of the respiratory tissues do contribute to the behaviour of the respiratory system. The SCM does not include a parameter for visco-elasticity so the contribution of viscoelasticity to energy dissipation is included in the estimates of resistance, elastance and inertance.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported that models which include terms for bronchial compliance, peripheral resistance, inhomogeneity or tissue properties may be superior to a SCM. 3,11,12 The visco-elastic tissue properties of the respiratory tissues do contribute to the behaviour of the respiratory system. The SCM does not include a parameter for visco-elasticity so the contribution of viscoelasticity to energy dissipation is included in the estimates of resistance, elastance and inertance.…”
Section: Discussionmentioning
confidence: 99%
“…Airway flow (9) was measured with a Fleisch #2 pneumotachograph connected to a differential piezoresistive transducer (Microswitch 163PC01D36, Honeywell, Tokyo, Japan). The pneumotachograph was, in turn, connected to a three-way valve which made it possible to switch between a mechanical ventilator (EVA-900, Aika, Tokyo, Japan) and a volume oscillator described elsewhere [4]. Tracheal pressure (Ptr) was measured by a piezoresistive pressure transducer (1CS 13 002G, ICSensors, Milpitas, CA, USA) at a side port of the tracheal cannula.…”
Section: Methodsmentioning
confidence: 99%
“…Zcw has the same structure as ZL except the lack in the resistance corresponding to R1 in ZL. Zvc has only one element of elastance Mechanical impedance of the respiratory system (ZRS) was measured in a frequency range between 0.15 and 6.65Hz bY a pseudorandom forced oscillation method as described previously [4,5]. Briefly, mechanical ventilation Was stopped at end expiration and the the intact subsystem which consists of lung with a resistance (RL) and an elastance (EL) enclosed by a chest wall.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations